LEGO Batman the Movie: DC Super Heroes Unite - Burton, Jon 1969-; Goodman, David A., 1975- (Burbank, CA Warner Home Video, 2013)
When Bruce Wayne receives the man of the year award, fellow billionaire Lex Luthor becomes jealous and decides to run for President. To create the atmosphere for his type of fear-based politics Lex recruits the Joker to perfect a Black LEGO Destructor Ray which wreaks havoc on Gotham. As Lex destroys Batmans tech, Batman reluctantly turns to Superman for help.
Title from container.
Originally released as a motion picture in 2013.
Special features: All-new featurette "Building Batman"; from the DC Comics vault: 3 bonus cartoons; a Lego Batman stop-motion short; Winning shorts from the LEGO DC Universe Super Heroes video contest.
Keywords: Juvenile films; Drama; Batman (Fictitious character) -- Juvenile films; Superheroes -- Juvenile films; Criminals -- Juvenile films; LEGO toys -- Juvenile films; Batman (Fictitious character) -- Drama; Superheroes -- Drama; Criminals -- Drama; LEGO toys -- Drama; DVD-Video discs; Childrens films; Animated films